TO THE ISSUES OF FORMATION OF NON-LINGUISTIC STUDENTS’ MOTIVATION FOR LEARNING ENGLISH - Salakhova Elza Zagirovna (Innovative Development in Educational Activities, 2023)
This article discusses the issue of formation of motivation among students of non-philological specialties in English learning process. The types of motivation are defined and compared, the advantages and disadvantages of each type are described. Practical recommendations are given to increase the level of motivation of students in the English learning process as a foreign language